2019
DOI: 10.1016/j.appet.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

“I will fast … tomorrow”: Intentions to restrict eating and actual restriction in daily life and their person-level predictors

Abstract: Objective. Dietary restraint is a common, yet controversial practice to tackle overweight. Yet, despite good intentions to reduce food intake, most restraint-based diets fail to produce long term weight loss. A better understanding of the naturalistic course of daily dieting intentions and their effectiveness in guiding subsequent eating behavior are therefore needed. Method. In two studies, participants (n=49 and n=59) reported both their state intention to restrict eating on the next day, as well as their ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…The current results might extend this finding in suggesting that the tendency of high stress eaters to increase their food intake on stressful days might in the long-term facilitate weight gain and a higher BMI, pointing to a state-trait interaction. Further corroborating this, recent research showed that SSES scores are related to intentionbehaviour-gaps with regard to restriction (Reichenberger et al, 2019): Participants with higher SSES scores exhibited higher intention-behaviour gaps in daily life in that they were more prone to report a higher intention to restrict compared to the actual restrictive behaviour. However, pathways towards BMI increase remain speculative unless examined longitudinally.…”
Section: Overall Discussionsupporting
confidence: 52%
“…The current results might extend this finding in suggesting that the tendency of high stress eaters to increase their food intake on stressful days might in the long-term facilitate weight gain and a higher BMI, pointing to a state-trait interaction. Further corroborating this, recent research showed that SSES scores are related to intentionbehaviour-gaps with regard to restriction (Reichenberger et al, 2019): Participants with higher SSES scores exhibited higher intention-behaviour gaps in daily life in that they were more prone to report a higher intention to restrict compared to the actual restrictive behaviour. However, pathways towards BMI increase remain speculative unless examined longitudinally.…”
Section: Overall Discussionsupporting
confidence: 52%
“…The latter assumption seemed to be supported by consumers' answers to the question about attention assigned to food quality (higher for Romanians). However, it should be considered that other factors besides interest (attention) intervene in explaining the use frequency of quality cues, similarly to the case of the intention-behavior gap for various food related behaviors [117,118].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FCQ-T-r scores moderated the relationship between craving for and consumption of these foods in that experiencing a craving more likely translated into consumption of snack foods in individuals with high FCQ-T-r scores than in those with low scores [3]. Scores on the FCQ-T-r also predicted a higher intentionbehavior gap in daily life as measured with ecological momentary assessment: those with higher FCQ-T-r scores were less likely to actually restrict their eating behavior on a given day when they intended to do so on the previous day [90]. Finallysimilar to the FCQ-T-discriminant validity is supported in that scores on the FCQ-T-r were unrelated to length of food deprivation (i.e., the time since the last meal [55,58]).…”
Section: Modified Versionsmentioning
confidence: 98%